Michael Ondaatje’s Anil’s Ghost:: Civil Wars, Mystics, and Rationalists - Bolland, John (Studies in Canadian Literature / Études en littérature canadienne, 2004)
In Anil's Ghost, Michael Ondaatje turns to alternative models of causality to explore the horrors of the Sri Lankan emergency, confounding the Western model of cause and effect with a narrative of events whose non-linear logic amounts to effect without cause. The presence of Buddhism in the novel allows Ondaatje to negotiate between postmodernist relativism and epiphanic insight into universal truths. Ondaatje's use of the Buddhist vision of the endless process of becoming and extinction, making dissolution paradoxically the principle of a higher form of cohesion, allows for a view of the world that includes a sense of fragmentation and the relativity of cultural truths.